RANCANG BANGUN APLIKASI BELAJAR ONLINE BERBASIS WEB SEBAGAI OPTIMALISASI PEMBELAJARAN UNTUK SISWA SMK - Adi Rahman (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2019)
The spread of massive internet connectivity and penetration of smart devices is a supporting factor why the approach of educational technology is an appropriate step. Currently online learning applications themselves are used for the public both from the level, elementary, junior high, to high school that students get at school can be learned through this online learning application. Now the more widespread online learning applications in Indonesia and more and more people are taking the initiative in making online-based learning with more interesting and creative features. However, no one has specifically developed a specific online learning application for students in vocational high schools. Their existence seems to be marginalized due to the community paradigm which assumes that vocational school children do not need alternative tutoring apart from teachers at school. Though they also need the same thing with high school students and others. Based on this analysis, researchers wanted to create a web-based online learning application for vocational students. Achievement Jack is an online learning application based on learning management system that allows students to be able to do learning through videos delivered by tutors. This study uses the Software Development Life Cycle (SDLC) waterfall type method, or hereinafter referred to as the waterfall method. Based on the above calculation, from 3 testers who filled out the questionnaire stated that this learning application was running with the results of testing the user interface 98%, the basic functions of the system 100%, and 100% validation. In conclusion, this application runs very well.